Comparison of Survival and Risk Factors of Differentiated Thyroid Cancer in the Geriatric Population - Yu, Lujiao; Hong, Hong; Han, Jinyu; Leng, Sean X.; Zhang, Haiyan; Yan, Xu (Frontiers in Oncology, 2020)
Purpose: The incidence rate of differentiated thyroid cancer (DTC), the most common type of thyroid cancer, has increased in past two decades. The present study analyzed the clinical and pathological characteristics of DTC and discussed the risk factors for survival in elderly age risk DTC patients. Methods: Elderly patients who were diagnosed with DTC and subsequently underwent surgery for DTC were identified from the SEER database (1988-2008). Based on histology, these patients were divided into C-PTC, FV-PTC and FTC. For these patients, the clinical characteristics, pathological features, and treatments undertaken were compared. Cox proportional hazards analysis was performed to evaluate the risk factors to disease-specific survival (DSS). Results: In the elderly DTC patients, FV-PTC shows intermediate tumor features compared to C-PTC and FTC, but presented a better outcome. Male, being African American, tumor size>4cm, extrathyroidal extension, lymph node metastasis, and distant metastasis were all strong risk factors for DSS in the elderly DTC patients (all p<0.05). No difference was found between lobectomy and total thyroidectomy with respect to DSS, and radiation therapy conferred no apparent advantage with respect to DSS (both p>0.05). Discussion: Patients with FV-PTC need more specific histology catalog and risk assessment, which suggested a conservative therapy. Risk stratification should be paid attention and treatment should be individualized for elderly patients.